Punjab in Prosperity and Violence : Administration, Politics and Social Change, 1947-1997 - Banga, Indu,; Grewal, J.S., (Brill | Manohar Publishers & Distributors, 2024)
Based on papers written for seminar on 'decolonization' and 'contemporary history' of the Punjab, organized by the Institute of Punjab Studies which aims at promoting inter-disciplinary study of the political, economic, social and cultural life of the peoples of the north-west of India, this book should be of great interest to administrators, politicians and journalists as well as to social scientists and general readers. It gives useful insights into administration, politics, violence, demographic change, and the condition of the relatively unprivileged 'fragments' of the society in the region - women, dalits, labourers and village communities.